Design and performance evaluation of underwater wireless sensor networks - Shi, Maqian (Nanyang Technological University, 2023)
This study investigates the position optimization problem for underwater wireless sensor networks. It aims to reduce the overall energy consumption and extend the lifetime of the network through clustering mechanism. We first derive the Single Cluster Head Allocation algorithm by deriving the equations for computing the optimal CH position in the case of a single cluster. Then based on the extension of the single cluster model, models for multiple clusters are introduced to reduce the total energy consumption step by step. The Multiple Cluster Head Allocation algorithms are summarized respectively. After theoretical analysis and experimental simulation, the correctness and superiority of the algorithms are proved. Thus an effective method is provided for the determination of cluster heads in UWSNs.